EKSTRAKSI MINYAK ESENSIAL BUNGA KAMBOJA PUTIH (Plumeria obtusa) DENGAN CO2 SUPERKRITIK: PENGARUH TEMPERATUR DAN TEKANAN - Arabella Febiola Armani; Ratna Frida Susanti (Jurnal Teknologi Industri Pertanian, 2023)
Plumeria obtusa frangipani flowers grow across Indonesia abundantly and are frequently used in Hindu religious ceremonies. However, fallen and used frangipani flowers could potentially cause an immense amount of flower waste on the ground and water. A preliminary study on the processing of the fresh flowers into essential oils by supercritical CO2 extraction had been done, however an evaluation of the extraction conditions (temperature and pressure) of P. obtusa has not yet performed. This work investigated the effect of extraction’s pressure (100 and 300 bar) and temperature (40 and 60 oC) to the essential oil’s yield and composition. The result showed that the high pressure of 300 bar and low temperature of 40oC gives the highest yield (0,736%) with 36 compounds identified. Among them, 81% of their biological and pharmacological activities and benefits had been reported (antibacterial, antifungal, aromatic compound, antioxidant, antimicrobial, anti-inflammatory). The identification of composition of the flower essential oils showed that olean-12-ene, 3-methoxy-, (3β) (35,12%) was found only at 300 bar and 40oC. This result confirmed that supercritical CO2 extraction was more specific in extracting volatile compounds from essential oils. Keywords: supercritical carbon dioxide, essential oil, oil yield, volatile compounds, Plumeria obtusa